Case report: Capillary hemangioma in the renal hilum mimicking paraganglioma - Jiang, Weixing; Liu, Xiaoqi; Wen, Li (Frontiers in Oncology, 2022)
Background: Capillary hemangioma is a common benign tumor in children. Its presence in the kidney is rare, and there have been only case reports in the English literature. Herein, we report a special case of capillary hemangioma located in the renal hilum, which was suspected to be a paraganglioma. Case presentation: A 44-year-old woman had an irregular mass in the right hilar region. She had a history of hypertension for 3 years, and her 24-hour urinary norepinephrine was slightly high (41.53 µg, normal range: 16.69-40.65 µg). Abdominal MRI revealed a mass in the renal hilum measuring approximately 4.8×4.0×3.2 cm, slightly low signal intensity on T1WI, and very high signal intensity both on T2WI and DWI. The multiphase enhanced scan showed that the tumor had obvious enhancement with a central hypointense area. Therefore, paraganglioma was initially diagnosed. Phenoxybenzamine was administered over the next 2 weeks. She received laparoscopic right hilar area tumor resection, and the kidney was preserved. Unexpectedly, the final pathology report was capillary hemangioma. Conclusions: Capillary hemangioma in the renal hilum is extremely rare. Surgery is the first choice to reduce the risk of compression symptoms and rule out malignancy in the setting of an undefined growing retroperitoneal mass. In addition, renal-sparing surgery should be preferred.